Metabolic disrupting effects of polychlorinated biphenyls revealed by long-term temporal variations of lipids in detritivorous fish from the Rio de la Plata Basin - Speranza, Eric Demian (2021)
The long-term covariation (2002-2017) of lipids, polychlorinated biphenyls (PCBs), and sewage tracers was studied in the detritivorous fish (Prochilodus lineatus) and settling detritus from the Rio de la Plata. Fatty fish from polluted Buenos Aires area (BA) exhibited a significant decrease of muscle lipids (71 ± 12 to 29 ± 8.6% dry weight;p< 0.0001), triglycerides (94 to 85%,p< 0.001), and 18 carbon fatty acids (18C-FA: 59 ± 4.8 to 48 ± 1.4%;p< 0.01), reflecting a reduction of lipid accumulation, largely triglycerides enriched in 18C-FA, with a concomitant ∼20-times decline of PCBs (∼20 to >1 μg g-1dw). The 2017 individuals of the BA series converged with leaner and more pristine northern fish (N), which showed no significant temporal variation (20 ± 10% lipids, 67 ± 8.7% triglycerides, 41 ± 8.1% 18C-FA, and 0.22 ± 0.42 μg g-1dw PCB). In contrast, the fecal sterol tracer coprostanol remained abnormally higher in BA fish muscle with no significant temporal trend (120 ± 102 vs 6.6 ± 10 μg g-1dw or 4.4 ± 2.8 vs 0.63 ± 1.2% sterols at N). The same pattern was observed in BA settling detritus, i.e., a temporal decrease of PCBs with high, stable coprostanol concentrations denoting sustained sewage inputs, while northern detritus was enriched in plant sterols. This long-term covariation of lipids and PCBs in fish muscle from polluted BA converging with more pristine and homogeneous northern specimens while maintaining a sewage-derived diet provides rare field evidence of the declining effect of PCBs controlling the temporal variation of muscular lipids in fish.